A financial network analysis of the equity linkages in Poland - Tomeczek, Artur F. (Finansowa analiza sieciowa powiązań kapitałowych w Polsce, 2021)
This article aimed to examine the financial networks of equity linkages and cross-shareholdings between publicly listed companies in Poland (WIG20 and mWIG40) and to explore the changes that occurred in bank ownership because of the COVID-19 pandemic. The literature review revealed four main types of financial networks: cross-shareholding, correlation, debt, and Granger-causality. Four equity-based directed financial networks were constructed. The two key network measures used in this research are PageRank (risk exposure and network importance) and modularity class (community detection).
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2021; vol. 65, nr 4, s. 129-143
Keywords: network analysis; equity linkages; PageRank; modularity; WIG; analiza sieciowa; powiązania kapitałowe; Warszawski Indeks Giełdowy